2020
DOI: 10.3389/fpls.2020.567388
|View full text |Cite
|
Sign up to set email alerts
|

A Microbial-Based Biostimulant Enhances Sweet Pepper Performance by Metabolic Reprogramming of Phytohormone Profile and Secondary Metabolism

Abstract: Microbial-based biostimulants can improve crop productivity by modulating cell metabolic pathways including hormonal balance. However, little is known about the microbial-mediated molecular changes causing yield increase. The present study elucidates the metabolomic modulation occurring in pepper (Capsicum annuum L.) leaves at the vegetative and reproductive phenological stages, in response to microbial-based biostimulants. The arbuscular mycorrhizal fungi Rhizoglomus irregularis and Funneliformis mosseae, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 65 publications
3
17
0
Order By: Relevance
“…This occurred despite the fact that at these thresholds the factors are considered to change “significantly”, and differences among treatments were mostly due to the presence of the inoculum and seen by a magnitude of the effect (+156% of Fe Uptake in the low stress and +53% in the high stress). In particular, AMF showed to be able to amply sustain the uptake of Fe-bound P by the plant [ 32 , 63 ] and some Trichoderma species showed to sustain P or Fe uptake by a siderophore production [ 64 , 65 , 66 , 67 ]. The role of the inoculum in the exclusion of the Na uptake in the high stress was higher than in the low stress.…”
Section: Discussionmentioning
confidence: 99%
“…This occurred despite the fact that at these thresholds the factors are considered to change “significantly”, and differences among treatments were mostly due to the presence of the inoculum and seen by a magnitude of the effect (+156% of Fe Uptake in the low stress and +53% in the high stress). In particular, AMF showed to be able to amply sustain the uptake of Fe-bound P by the plant [ 32 , 63 ] and some Trichoderma species showed to sustain P or Fe uptake by a siderophore production [ 64 , 65 , 66 , 67 ]. The role of the inoculum in the exclusion of the Na uptake in the high stress was higher than in the low stress.…”
Section: Discussionmentioning
confidence: 99%
“…PHs and AMF biostimulant had positive effects on biomass, phytohormones production and improved tolerance to reactive oxygen species (ROS)-mediated oxidative imbalance. Likewise, [ 75 ] demonstrated a clear link between endophytic fungi - mediated yield increase in pepper plants and a strong up-regulation of phytohormones. Moreover, metabolomics analysis highlighted the molecular basis of the improved loquat plant growth in the presence of the root rot fungus Armillaria mellea following AMF colonization [ 116 ].…”
Section: Targeted and Untargeted Approaches To Soil Microbial Diversity Managementmentioning
confidence: 99%
“…In general, plants produce natural defense substances like PSC after biotic or abiotic stress exposure, mainly depending on plant genotype, but their expression may be modulated by various different agronomic and environmental factors, including crop interaction with rhizosphere microbes [ 135 , 136 ]. For instance, the metabolomic analyses disclosed a clear link between AMF and PGPR inoculation in pepper and basil respectively, increased crops yield and the accumulation of several PSC associated with crop defense to environmental stresses [ 75 , 138 ]. Similarly, the metabolome analysis revealed that olive growing in fields where no-tillage and crop residue cover were applied, shown higher PSC concentration in xylem sap [ 139 ].…”
Section: Implications Of Soil Biodiversity For Nutrition and Food Safetymentioning
confidence: 99%
“…Omics sciences, particularly metabolomics, are emerging as indispensable approaches in decoding the mechanisms of action employed by biostimulants ( Nephali et al, 2020 ). Recent metabolomics studies have shown that a microbial biostimulant increased the yield of sweet pepper by inducing a metabolic readjustment of hormones and secondary metabolism ( Bonini et al, 2020 ). Furthermore, some of the currently elucidated molecular changes underlying microbial-induced systemic resistance against drought stress include (i) the production of phytohormones, siderophores, volatiles and osmolytes, (ii) the enhanced antioxidant defense system and (iii) 1-aminocyclopropane-1-carboxylate (ACC) deaminase activity and exopolysaccharides (EPS) production ( Ahemad and Kibret, 2014 ; Vurukonda et al, 2016 ; Prasad et al, 2017 ; Bhat et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%